Clinical, Histologic, and Molecular Characteristics of Anaplastic Lymphoma Kinase-positive Primary Cutaneous Anaplastic Large Cell Lymphoma. (June 2020) - Melchers, Rutger C.; Willemze, Rein; van de Loo, Merel; van Doorn, Remco; Jansen, Patty M.; Cleven, Arjen H.G.; Solleveld, Nienke; Bekkenk, Marcel W.; van Kester, Marloes S.; Diercks, Gillis F.H.; Vermeer, Maarten H.; Quint, Koen D.
Abstract : Unlike systemic anaplastic large cell lymphoma, the vast majority of primary cutaneous anaplastic large cell lymphomas (C-ALCL) do not carry translocations involving the ALK gene and do not express ALK. Expression of ALK protein therefore strongly suggests secondary cutaneous involvement of a systemic anaplastic large cell lymphoma. Recent studies described a small subgroup of ALK-positive C-ALCL, but information on frequency, prognosis, and translocation partners is virtually lacking. A total of 6/309 (2%) C-ALCL patients included in the Dutch registry for cutaneous lymphomas between 1993 and 2019 showed immunohistochemical ALK expression. Clinical and histopathologic characteristics, immunophenotype and disease course were evaluated. Underlying ALK translocations were analyzed with anchored multiplex polymerase chain reaction-based targeted next-generation sequencing. Median age at diagnosis was 39 years (range: 16 to 53 y). All patients presented with a solitary lesion. Treatment with radiotherapy (n=5) or anthracycline-based chemotherapy (n=1) resulted in complete responses in all 6 patients. Three patients developed a relapse, of whom 2 extracutaneous. After a median follow-up of 41 months, 5 patients were alive without disease and 1 patient died of lymphoma. Immunohistochemically, 3 cases (50%) showed combined nuclear and cytoplasmic ALK expression with underlying NPM1-ALK fusions, while 3 cases (50%) showed solely cytoplasmic ALK expression with variant ALK fusion partners ( TRAF1, ATIC, TPM3 ). ALK-positive C-ALCL is extremely uncommon, has a comparable favorable prognosis to ALK-negative C-ALCL, and should be treated in the same way with radiotherapy as first-line treatment.